NOTE ON THE POISON PRODUCED BY THE POLYDESMUS (FONTARIA) VICINUS LIN ARCH - PALLARES SODI, ERNESTO (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1965)
A systematic revision of the spp of the genus Megalodiscus is given M montezumae Travassos, 1934 is reduced to synonymy under M temperatus (Stafford, 1905) M rankini is described A key and comparative chart of the species is given
BIOCHEM J
Keywords: NOTE, POISON, POLYDESMUS, FONTARIA, VICINUS; MULTIDISCIPLINARIA; OTRAS ESPECIALIDADES MEDICAS (ESPECIFICAR); MEDICINA BIOQUIMICA